[PP.13.17] GENDER DIFFERENCES IN BLOOD PRESSURE CONTROL IN HYPERTENSIVE PATIENTS. (September 2016) - Radchenko, G.; Salascheva, T.; Mushtenko, L.; Sirenko, Y.
Abstract : Objective: The aim of study was to compare blood pressure (BP) control in Ukrainian hypertensive patient population and define the factors, which associated with failed BP control during 3-month antihypertensive therapy in men and women. Design and method: 9821 patients (58.9 ± 0.24yrs) with BP>140/90 mmHg were included in 3-month multicenter open trial. All patients were divided in groups: 1st–5944 female; 2nd–3877 men. Patients were treated by primary care physicians, who prescribed drugs according to their own view. Patients were done on 4 visits: office BP measurements, ECG, patient's compliance and cardiovascular risk evaluations by standard tests, inquiring by author's questionnaire. Multifactor regression analysis was used for evaluation of antihypertensive treatment failure predictors. Results: In women, in comparison with men, arterial hypertension was associated with more frequent heart failure (48.4 vs 45.8%, p = 0.02), stroke (17.8 vs 15.8%, p = 0.02), diabetes mellitus (15.2 vs 12.1 %, p < 0.001), renal damage (23 vs 20.4%, p = 0.005), obesity (37.1 vs 21%, p < 0.001), poor inheritance (65.6 vs 63.3 %, p = 0.02), older age (60.1 ± 0.23 vs 58.5 ± 0.3yrs, p < 0.001), high systolicBP (166.4 ± 0.24 vs 165.2 ± 0.27 mmHg, p = 0.001). The men had more frequently the history of myocardial infarction (15.6 vs 6.2%, p < 0.001) and bad habits (smoking, alcohol and salt abusing). The physical activity rate was more in men (57.2 vs 47.7%, p < 0.001). Baseline only 23.6% of 1st-group and 20.9% of 2nd-group (p < 0.01) had high drug compliance. During the therapy in both groups we noted improving of patient compliance, but at the end of study more men were characterized as incompliant, than women (27.1 vs 31.4%, p < 0.001). In women BP control after 3-month therapy was worse than in men (50.6 vs 58.3%, p < 0.001).Common factors for both groups associated with poor BP control were age, baseline BP levels, low baseline and on-treatment patient compliance, absence of status "working". In women high BMI was associated with poor BP control (β = 1.025, p = 0.003), while fresh vegetable/fruit consumption – with success treatment (β = 0.63, p = 0.002). Only in men additional physical activity decreased the probability of failed BP control (β = 0.78, p = 0.02). Conclusions: BP control was better in men, than in women, in spite of better compliance in women. In women it is necessary life-style modification with decreasing of BMI and increasing of vegetable/fruit consumption. In men it is necessary to pay attention for increasing of physical activity and drug compliance. Older patients of both genders with baseline higher BP and who do not work need to be included in group of more tight management.